Close encounters of the US kind: illness and injury among US athletes at the PyeongChang 2018 Winter Olympic Games. Issue 16 (2nd August 2019) - Nabhan, Dustin; Windt, Johann; Taylor, David; Moreau, William
Abstract : Aim: To describe injury and illness incidence during the 2018 Winter Olympic Games (WOG) by Team USA. Methods: A descriptive observational study. We used registered Team USA Olympic athletes' electronic medical records to review preparticipation health histories and medical encounters immediately prior to and throughout the 2018 WOG. Medical encounters were defined as all medical services provided by a healthcare provider, including evaluation, treatment and prophylactic services. All medical conditions were described according to International Olympic Committee injury and illness reporting criteria. Results: Team USA included 134 men and 108 women, aged 18–39 years, who represented 17 sport federations. The 47 Team USA medical staff documented 1744 medical encounters on 242 registered athletes (7.2 medical encounters per athlete). Forty-seven illnesses (194.2/1000 athletes) and 32 time loss injuries (132.2/1000 athletes) were recorded during the Games. Conclusions: An injury surveillance programme consisting of an electronic preparticipation health history and surveillance of medical encounters during the WOG was used to describe the health status of Team USA. We noted limitations to the surveillance process that can be addressed at future events.